Impact of circ-0000221 in the Pathogenesis of Hepatocellular via Modulation of miR-661-PTPN11 mRNA Axis - Marwa Matboli; Mohmed Kamal Hassan; Mahmoud A. Ali; Mohamed Tarek Mansour; Waheba Elsayed; Reham Atteya; Hebatallah Said Aly; Mahmoud El Meteini; Hesham Elghazaly; Sherif El-Khamisy; Sara H. A. Agwa (MDPI AG, 2022)
Hepatocellular carcinoma (HCC) is a leading cause of cancer-related death in Egypt. A deep understanding of the molecular events occurring in HCC can facilitate the development of novel diagnostic and/or therapeutic approaches. In the present study, we describe a novel axis of hsa-circ-0000221-miR-661-PTPN11 mRNA proposed by in silico and in vitro analysis and its role in HCC pathogenesis. We observe a reduction in the expression levels of hsa-circ-0000221 and PTPN11 mRNA in HCC patients' sera tested compared with control subjects. The reduction occurs with a concomitant increase in the expression of miR-661. Furthermore, the introduction of exogenous hsa-circ-0000221 into Hep-G2 or SNU449 cell lines results in detectable decrease in cellular viability and an increase in apoptotic manifestations that is associated with G1 accumulation and CCDN1 overexpression. Altogether, these findings indicate the tumor-suppressive role of hsa-circ-0000221 in HCC, which acts through miR-661 inhibition, along with a subsequent PTPN11 mRNA increase, where PTPN11 is known to inhibit cell proliferation in many forms of cancer. Our study encourages further investigation of the role of circRNAs in cancer and their potential use as molecular biomarkers.